Hippocampal-dependent appetitive control is impaired by experimental exposure to a Western-style diet. Issue 2 (19th February 2020) - Stevenson, Richard J.; Francis, Heather M.; Attuquayefio, Tuki; Gupta, Dolly; Yeomans, Martin R.; Oaten, Megan J.; Davidson, Terry
Abstract : Animals fed a Western-style diet (WS-diet) demonstrate rapid impairments in hippocampal function and poorer appetitive control. We examined if this also occurs in humans. One-hundred and ten healthy lean adults were randomized to either a one-week WS-diet intervention or a habitual-diet control group. Measures of hippocampal-dependent learning and memory (HDLM) and of appetitive control were obtained pre- and post-intervention. HDLM was retested at three-week follow-up. Relative to controls, HDLM performance declined in the WS-diet group ( d = 0.43), but was not different at follow-up. Appetitive control also declined in the WS-diet group ( d = 0.47) and this was strongly correlated with HDLM decline ( d = 1.01). These findings demonstrate that a WS-diet can rapidly impair appetitive control in humans—an effect that could promote overeating in consumers of a WS-diet. The study also suggests a functional role for the hippocampus in appetitive control and provides new evidence for the adverse neurocognitive effects of a WS-diet.